A new approach to estimating coal gas content for deep core sample. (1st October 2020) - Xu, Hongjie; Pan, Zhejun; Hu, Baolin; Liu, Huihu; Sun, Gui
Abstract: Method to accurately estimate gas content in the deep-burial coals is still unavailable. To this end, a new method which avoids the underestimation of lost gas content during the retrieval process of deep-burial coal sample within boreholes was well established in the text. This method, which is based on nonlinear curve-fit of measured gas content, contains two parameters to be determined. The two key parameters, referred to the lost gas and total gas, were precisely determined through the best matching with the experimental data with the aid of additional residual gas as a part of the total desorbed gas. As a case study, a suggested error analysis method was used to verify the accuracy of the lost gas of two coal cores based on extended desorption data more than 1 000 min or field customized data of 120 min including the supplemental data of residual gas. Utilizing the present method to calculate the gas content of fifteen core coal samples with standard field cases in the study area, the calculated lost gas and total gas content are 0.88–1.54 times and 1.15–1.96 times with an average of 1.17 and 1.47 times of the measured values obtained by the direct method, respectively. The new method offers an accurate estimation of gas content, which has a wide application potential that the traditional methods are not applicable for deep-burial coal seam.